Assessment of compliance with iron-folic acid therapy during pregnancy among postnatal mothers in a tertiary care centre, Mysuru - K., Manasa; S. G., Chandrakumar; B., Prashantha (International Journal Of Community Medicine And Public Health, 2019)
Background: Anemia is a condition where the red blood cells and their capacity to carry oxygen is not adequate to meet the physiological needs. In pregnancy iron demand is high and loss of appetite can adversely affect this condition. So, guidelines to combat anemia has provisions to provide iron in the form of iron folic acid tablets to pregnant women during antenatal and postnatal care. But compliance is still low among pregnant women who needs attention. Methods: This study included 192 postnatal mothers in Cheluvamba hospital, Mysore. Details about socio-demographic factors and number of tablets taken during antenatal period were collected using proforma. Pregnant women who had taken less than hundred tablets during antenatal period were considered non-compliant. Results: The overall compliance to iron folic tablets was 71%. The factors which were independently associated with non-compliance are nuclear family, less number of antenatal visit, tablets from private source, and anemia in current pregnancy. The reasons for non-compliance among the pregnant women who were non-compliant were inadequate counselling by health care worker followed by side effects, cost of tablets, ignorance and fear of side effects. Conclusions: Family support, adequate counselling and continuous supply of tablets free of cost would increase the compliance to tablets among pregnant women.